(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2010)
A financial analysis tool such as financial rations concentrates on explanation of financial statement and using them in the evaluation of company profiles and fixing taxable profits, by analyzing final calculation, explaining their results and studying relationships between a group of financial lists ’elements in a specific period and the trend of their relationships in percentage from so, financial analysis is considered on important instrument for tax analytical test procedures through studying and evaluating financial data in order to get proper information which is needed to make sure of credibility and reliability of statements submitted by the taxpayer and the satisfaction of the tax analyzer in the credibility of these statements and their accuracy. And in knowing company ’financial situation and result of its activity and measuring and fixing taxable income by scientific way to dedicative a new standard will help to collocate tax income in realistic way can be achieved the satisfaction and credibility in tax settlement of taxpayer and the financial authority.